Direct evidence for the Homo-Pan clade - Wimmer, Rainer; Kirsch, Stefan; Rappold, Gudrun; Schempp, Werner (Chromosome research, 2002)
For a long time, the evolutionary relationship between human and African apes, the 'trichotomy problem', has been debated with strong differences in opinion and interpretation. Statistical analyses of different molecular DNA data sets have been carried out and have primarily supported a Homo—Pan clade. An alternative way to address this question is by the comparison of evolutionarily relevant chromosomal breakpoints. Here, we made use of a P1-derived artificial chromosome (PAC)/bacterial artificial chromosome (BAC) contig spanning approximately 2.8 Mb on the long arm of the human Y chromosome, to comparatively map individual PAC clones to chromosomes from great apes, gibbons, and two species of Old World monkeys by fluorescence in-situ hybridization. During our search for evolutionary breakpoints on the Y chromosome, it transpired that a transposition of an approximately 100-kb DNA fragment from chromosome 1 onto the Y chromosome must have occurred in a common ancestor of human, chimpanzee and bonobo. Only the Y chromosomes of these three species contain the chromosome-1-derived fragment; it could not be detected on the Y chromosomes of gorillas or the other primates examined. Thus, this shared derived (synapomorphic) trait provides clear evidence for a Homo—Pan clade independent of DNA sequence analysis.
Gesehen am 07.04.2021